2022
DOI: 10.1002/jmv.28001
|View full text |Cite
|
Sign up to set email alerts
|

Prevotella as the hub of the cervicovaginal microbiota affects the occurrence of persistent human papillomavirus infection and cervical lesions in women of childbearing age via host NF‐κB/C‐myc

Abstract: There is evidence that coinfection of cervicovaginal high-risk human papillomavirus (HR-HPV) and bacteria is common in women of childbearing age. However, the relationship between bacterial vaginosis (BV) and persistent HR-HPV infection in women of childbearing age and the underlying mechanisms remain unclear. In this study, we determined whether BV affects persistent HR-HPV infection in women aged 20-45 years and explored the possible mechanisms of their interactions. From January 1 to April 30, 2020, we recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…NOD1 and NOD2 can recognize intracellular PAMPs that can enter the cell through phagocytosis or membrane pores (Anton et al, 2022). BV and associated pathogens, such as Prevotella and Gardnerella, have been shown that associated with the expressions of TLRs and NLRs, especially TLR2/4 (Anahtar et al, 2015;Anton et al, 2022;Dong et al, 2022;Gerson et al, 2022). BV-associated bacteria can induce immune response of cervical cells through the TLR2/4−activated signalling pathways (Zariffard et al, 2005;Anton et al, 2022).…”
Section: Immune Response Induced By Cervicovaginal Microbiota On Cervixmentioning
confidence: 99%
See 1 more Smart Citation
“…NOD1 and NOD2 can recognize intracellular PAMPs that can enter the cell through phagocytosis or membrane pores (Anton et al, 2022). BV and associated pathogens, such as Prevotella and Gardnerella, have been shown that associated with the expressions of TLRs and NLRs, especially TLR2/4 (Anahtar et al, 2015;Anton et al, 2022;Dong et al, 2022;Gerson et al, 2022). BV-associated bacteria can induce immune response of cervical cells through the TLR2/4−activated signalling pathways (Zariffard et al, 2005;Anton et al, 2022).…”
Section: Immune Response Induced By Cervicovaginal Microbiota On Cervixmentioning
confidence: 99%
“…addition to tryptophan depletion, a recent study found that IFN-g also can down regulate c-Myc, the key regulator of host cell metabolism, resulting in the reduction of TCA cycle intermediates and nucleotides to prevent chlamydial replication and promoting persistence (Rajeeve et al, 2020;Vollmuth et al, 2022). Constitutive expression of c-Myc can rescue CT from persistence induced by IFN-g. Dong et al (Dong et al, 2022) proved that the abundance of Prevotella correlates with the expression of cervical TLR4, NF-kB, C-myc, and hTERT genes. In contrast, Lactobacillus abundance showed negative correlations with these genes.…”
Section: The Effect Of Cervicovaginal Microbiota On Sti Infection Ct ...mentioning
confidence: 99%
“…Overgrowth of Prevotella sp. in the vagina has been linked to the development of cervical lesions caused by persistent Hr-HPV infection by influencing host NF-κB and C-myc signaling pathways [ 45 ]. In addition, Atopobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…The cervicovaginal microbiota may alter STI symptomatology, particularly the presence of vaginal discharge and discomfort, or in the case of HPV, viral persistence or development of preneoplastic lesions within the genital tract [91 ▪▪ ] (reviewed in [92]). These symptoms may bias towards STI test seeking behavior, at least for certain STI pathogens, since symptoms of localized inflammation in the genital tract are typical of both cervicovaginal dysbiosis (e.g., BV) and pathogens like N. gonorrhoeae , C. trachomatis , M. genitalium , and Trichomonas vaginalis .…”
Section: The Genital Microbiome Influences Sexually-transmitted Infec...mentioning
confidence: 99%
“…Vaginal microbiotas dominated by L. crispatus and/or L. gasseri have been associated with a decreased risk of HPV CIN3 progression [78,80] and persistence [79,81]. Prevotella has been implicated in persistence of high-risk HPV types and associated with higher expression of oncogenic and inflammatory markers [91 ▪▪ ].…”
Section: The Genital Microbiome Influences Sexually-transmitted Infec...mentioning
confidence: 99%